A Rare Case of an Ophthalmologic Emergency: Idiopathic Central Retinal Artery Occlusion - Maryam, Abdulla, (International Journal of Innovative Research in Medical Science, 2018)
Central retinal artery occlusion is a form of an acute stroke in the eye and is regarded as an ophthalmic emergency.[1,2] This paper presents a case of Central retinal artery occlusion in an 18-year-old pregnant female who presented with sudden loss of vision in her right eye and was diagnosed with central retinal artery occlusion. The aim of this paper is to illustrate the clinical presentation, diagnosis and treatment but mainly focusing on the underlying etiologies. Recent literature shows no reported cases explaining the possibility of retinal artery occlusion occurring in a young pregnant female who is otherwise free of any medical conditions.[3] Due to the serious consequence, limited knowledge and treatment in the field of unexplained retinal occlusion in pregnancy; it’s encouraged that more efforts are invested in research and reporting cases for a better understanding of the possible and future management options and preventative strategies of central retinal occlusions.